ICTs and School Education - Aris, Nuria; Orcos, Lara (International Journal of Interactive Multimedia and Artificial Intelligence, 2017)
Nowadays, there exist lots of ICTs that teachers use as teaching tools. In this work, we introduce the theoretical context of the study of using ICTs in school education, then we present the method that will be used in order to achieve our goals. This work constitutes the groundwork to continue the study of ICT and its use in teaching.
Keywords: ICTs; School Education; teaching paradigms; Emerging; IJIMAI